Henry and Mudge and the Tall Tree House : The Twenty-first Book of Their Adventures - Rylant, Cynthia; Bracken, Carolyn (New York : Simon & Schuster Books for Young Readers, 2002)
Henry is excited when his Uncle Jake builds him a tree house but worries that his dog Mudge will not be able to enjoy it with him.
Keywords: Tree houses -- Fiction; Dogs -- Fiction; Uncles -- Fiction